2016
DOI: 10.1186/s12877-016-0256-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions to indirectly support food and drink intake in people with dementia: Eating and Drinking Well IN dementiA (EDWINA) systematic review

Abstract: BackgroundRisks and prevalence of malnutrition and dehydration are high in older people but even higher in older people with dementia. In the EDWINA (Eating and Drinking Well IN dementiA) systematic review we aimed to assess effectiveness of interventions aiming to improve, maintain or facilitate food/drink intake indirectly, through food service or dining environment modification, education, exercise or behavioural interventions in people with cognitive impairment or dementia (across all settings, levels of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(123 citation statements)
references
References 83 publications
3
114
0
6
Order By: Relevance
“…In contrast, a recent study found that the perceptions of the quality of the dining environment and the quality of the meal have very limited influence on intake (Buckinx, Morelle, & Bruyère, ). The finding is consistent with systematic reviews reporting that modification of dining environments or routines including tableware and table setting visual contrast (Brush, Meehan, & Calkins, ), noise reduction (McDaniel, Hunt, Hackes, & Pope, ), lighting enhancement (Brush et al, ; McDaniel et al, ), bulk food delivery service (Desai, Winter, Young, & Greenwood, ), family‐style meals (Altus, Engelman, & Mathews, ), smoothing or re‐creative music (Mc Hugh, ) have low level of evidence in improving meal intake (Abbott et al, ; Bunn et al, ; Liu, Watson et al, ). With the mixed results, the role of environmental factors on intake in dementia deserves further investigation.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…In contrast, a recent study found that the perceptions of the quality of the dining environment and the quality of the meal have very limited influence on intake (Buckinx, Morelle, & Bruyère, ). The finding is consistent with systematic reviews reporting that modification of dining environments or routines including tableware and table setting visual contrast (Brush, Meehan, & Calkins, ), noise reduction (McDaniel, Hunt, Hackes, & Pope, ), lighting enhancement (Brush et al, ; McDaniel et al, ), bulk food delivery service (Desai, Winter, Young, & Greenwood, ), family‐style meals (Altus, Engelman, & Mathews, ), smoothing or re‐creative music (Mc Hugh, ) have low level of evidence in improving meal intake (Abbott et al, ; Bunn et al, ; Liu, Watson et al, ). With the mixed results, the role of environmental factors on intake in dementia deserves further investigation.…”
Section: Introductionsupporting
confidence: 81%
“…As gender and dementia stage are less modifiable, improving eating performance, the most fundamental ADL among residents (Liu, Unick, Galik, & Resnick, 2015), has been a focus of recent intervention research. Montessori-based activities and spaced retrieval trainings targeting older adults with dementia (Wu, Lin, Wu, Lin, & Liu, 2014) and staff mealtime assistance with a strong social interaction component (standardized verbal prompts, positive reinforcement, appropriate encouragement; Coyne & Hoskins, 1997;Van Ort & Phillips, 1995) have showed some evidence in decreasing feeding difficulty and improving eating performance Bunn et al, 2016;Liu, Galik, Boltz, Nahm, & Resnick, 2015a, 2015bLiu, Watson et al, 2014). Future work needs to test the impact of these strategies on the pace and amount food intake in dementia.…”
Section: Resident Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Programs to improve the meals of residents and aid in their health recovery have been reported; these programs are generally focused on the transition from gastric tube feeding to oral feeding or nutritional supplementation [10,11]. Further efforts are needed to enable senior residents to eat foods with consistencies close to those of regular foods.…”
Section: Introductionmentioning
confidence: 99%
“…The management of symptoms relating to dementia will vary dependent on the care setting. Previous systematic reviews in this area have focused on randomised controlled trials (RCTs) carried out across all care settings (residential care facility, hospital ward environments and own homes), but to date have included minimal analysis of studies specific to “own home” (Abdelhamid et al., ; Bunn et al., ). Carer surveys have indicated that there is a need for increased primary care support relating to the nutritional needs and consequences associated with dementia in those living at home (Alzheimer's Society, ).…”
Section: Introductionmentioning
confidence: 99%